Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3389/fcell.2021.795460
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Sepsis on High-Density Lipoprotein Metabolism

Abstract: Background: High-density lipoproteins (HDL) are thought to play a protective role in sepsis through several mechanisms, such as promotion of steroid synthesis, clearing bacterial toxins, protection of the endothelial barrier, and antioxidant/inflammatory activities. However, HDL levels decline rapidly during sepsis, but the contributing mechanisms are poorly understood.Methods/Aim: In the present study, we investigated enzymes involved in lipoprotein metabolism in sepsis and non-sepsis patients admitted to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 50 publications
1
19
0
Order By: Relevance
“…The major functions of human SAA are associated with amyloidogenesis, the remodeling of HDL, tumor pathogenesis, anti-bacterial functions, and regulation of inflammation and immunity [ 105 ]. In sepsis, patients in the critical phase showed that the HDL-C level decreased to approximately 14 mg/dL, while SAA sharply elevated to around 2827 μg/mL, in contrast to the control group that showed a normal level of HDL-C (~39 mg/dL) and 269 μg/mL of SAA [ 106 ]. SAA is expressed almost exclusively in the liver and is triggered by pro-inflammatory cytokines.…”
Section: Hdl Qualitymentioning
confidence: 99%
“…The major functions of human SAA are associated with amyloidogenesis, the remodeling of HDL, tumor pathogenesis, anti-bacterial functions, and regulation of inflammation and immunity [ 105 ]. In sepsis, patients in the critical phase showed that the HDL-C level decreased to approximately 14 mg/dL, while SAA sharply elevated to around 2827 μg/mL, in contrast to the control group that showed a normal level of HDL-C (~39 mg/dL) and 269 μg/mL of SAA [ 106 ]. SAA is expressed almost exclusively in the liver and is triggered by pro-inflammatory cytokines.…”
Section: Hdl Qualitymentioning
confidence: 99%
“…Reconstituted HDL (rHDL) was prepared using the sodium cholate dialysis method [47] at an initial molar ratio of 95:5:1:0, 95:5:1:0.5, 95:5:1:1, and 95:5:1:2 for POPC:cholesterol:apoA-I:SAA, respectively. The physiological concentration of SAA, around 0.269 mg/mL [10], was mimicked using 0.23 mg and 0.46 mg of SAA for the 1:0.5 and 1:1 molar ratio, respectively, of apoA-I:SAA in 1 mL. The size and hydrodynamic diameter of the rHDL particles were determined by 8-25% native polyacrylamide gradient gel electrophoresis (PAGGE, Pharmacia Phast system) and by a comparison with standard globular proteins (GE healthcare, Cat# 17-0445-01).…”
Section: Synthesis Of Reconstituted Hdlmentioning
confidence: 99%
“…Circulating SAA plays a critical role in various inflammatory diseases, including sepsis, atherosclerosis, and rheumatoid arthritis [9]. In sepsis, patients in the critical phase showed that the HDL-C level was decreased to approximately 14 mg/dL, while SAA was elevated sharply around 2827 µg/mL, while the control group showed a normal level of HDL-C (~39 mg/dL) and 269 µg/mL of SAA [10]. SAA is expressed almost exclusively in the liver and released into the bloodstream.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HDL-C levels had the strongest correlation with IL-6 and procalcitonin levels, as well as sequential organ failure assessment [ 30 ]. HDLs are thought to play a protective role in sepsis as alterations in HDL metabolism, such as a decrease in lecithin-cholesterol acyl transferase activity and concentration, cholesteryl transfer protein activity, or an increase in phospholipid transfer activity protein and endothelial lipase activity, occur early after the development of sepsis [ 31 ]. Because of its early decrease and high stability, HDL-C is considered to be an independent predictive marker of adverse outcomes and survival in severe sepsis [ 32 ].…”
Section: Membrane and Serum Cholesterol And Their Roles During Infectionmentioning
confidence: 99%